Evaluation of the hydraulic clutches introduction for centrifugal pumps productivity control - Иванов, Вадим Борисович; Ситас, Виктор Иванович; Рихтер, Мартин (Technology audit and production reserves, 2015)
The problems of the effectiveness of controlled hydrodynamic drives for performance control of centrifugal pumps are considered in the article. The advantages of this technology are shown. They are consists in saving investment cost, high reliability, durability and technical readiness, ease of maintenance and service equipment. Examples of calculations of energy savings for the pumps of various capacities are given. The factors which have the most significant impact on the payback period in the implementation of this technology are analyzed. As the initial information about the required investment and the savings of resources is used data on the implementation of the drives in the thermal energy sector of the CIS countries, including Zaporozhye, Kurakhovo, Starobeshevo TPP, TPP-5 and TPP-6, as well as the power plants of "Kyivenergo". Results of the analysis allow determining priority types of centrifugal pumps. It is advisable to equip the hydrodynamic drive. These include nutritional, network, oil, sludge and other heavy-duty centrifugal pumps, also having high speed and running most of the time at part load.